Tannic acid: a crosslinker leading to versatile functional polymeric networks: a review - Chen, Chen; Yang, Hao; Yang, Xiao; Ma, Qinghai (RSC advances, 2022)
With the thriving of mussel-inspired polyphenol chemistry as well as the demand for low-cost analogues to polydopamine in adhesive design, tannic acid has gradually become a research focus because of its wide availability, health benefits and special chemical properties. As a natural building block, tannic acid could be used as a crosslinker either supramolecularly or chemically, ensuring versatile functional polymeric networks for various applications. Up to now, a systematic summary on tannic-acid-based networks has still been waiting for an update and outlook. In this review, the common features of tannic acid are summarized in detail, followed by the introduction of covalent and non-covalent crosslinking methods leading to various tannic-acid-based materials. Moreover, recent progress in the application of tannic acid composites is also summarized, including bone regeneration, skin adhesives, wound dressings, drug loading and photothermal conversion. Above all, we also provide further prospects concerning tannic-acid-crosslinked materials. With the thriving of mussel-inspired chemistry and the demand for low-cost analogues to polydopamine in adhesive design, tannic acid has become a research focus because of its wide availability, health benefits and special chemical properties.